2020
DOI: 10.3390/w12102800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Cover and Atmospheric Input on Nutrient Budget in Subtropical Mountainous Rivers, Northeastern Taiwan

Abstract: The nutrient budget, the difference between the nutrient output via stream and input via precipitation, can provide insights into how environmental processes affect forested ecosystem biogeochemistry. In this study, field measurements of the nutrient budgets—including Na+, Cl−, K+, Mg2+, Ca2+, NO3−, and SO42−—of 19 sites were conducted in Feitsui Reservoir Watershed (FRW) of northeastern Taiwan. A series of power-law regressions were developed to establish the relationship of the nutrient budget to the dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Although nutrient cycling and nutrient limitations do play an important role in tree growth in the (sub)‐tropical forest biomes (Houlton et al., 2008), nitrogen (N) and phosphorous (P) cycling are not accounted for in ORCHIDEE r4262. The abundance of dissolved inorganic nitrogen in the river discharge (Chang et al., 2020; Huang et al., 2016) suggests that nitrogen is no longer a factor limiting plant growth over large areas of Taiwan. The primary source of this nitrogen is likely atmospheric deposition from emissions from mainland China, and from local industry and households, estimated to be between 0.8 and 20 kg N ha −1 yr −1 (Zhao et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although nutrient cycling and nutrient limitations do play an important role in tree growth in the (sub)‐tropical forest biomes (Houlton et al., 2008), nitrogen (N) and phosphorous (P) cycling are not accounted for in ORCHIDEE r4262. The abundance of dissolved inorganic nitrogen in the river discharge (Chang et al., 2020; Huang et al., 2016) suggests that nitrogen is no longer a factor limiting plant growth over large areas of Taiwan. The primary source of this nitrogen is likely atmospheric deposition from emissions from mainland China, and from local industry and households, estimated to be between 0.8 and 20 kg N ha −1 yr −1 (Zhao et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For nutrient-associated impacts, the nutrient export is strongly affected by the source locality and pathway condition (reaction condition in rivers). Chang et al 2020 and Lee et al 2020 [10,11] attempted to use the nutrient budget and statistical analysis to identify the source locality of different nutrients. Their results showed that agricultural land and atmospheric input are the main sources of nutrients.…”
Section: Summary Of This Special Issuementioning
confidence: 99%